Longitudinal Changes in Social Brain Development: Processing Outcomes for Friend and Self. Issue 6 (11th November 2016) - Braams, Barbara R.; Crone, Eveline A.
Abstract : Adolescence is an important time for social development during which friendships become more intimate and complex. In this functional magnetic resonance imaging (fMRI) study we tested how outcomes for friends are processed on the neural level across adolescence. Participants between 8 and 27 years of age were tested twice with a 2‐year difference between the first ( N = 299) and second ( N = 254) time points. Participants performed a task in which they could win and lose money for themselves and their best friend. Mixed linear models revealed a linear decrease in activity in social brain regions for friend > self over development. These results confirm changes in the social brain network across adolescent development, we further show that individual differences are related to these neural changes.